The clinical utility of next-generation sequencing for bone and soft tissue sarcoma. (2nd January 2022) - Gusho, Charles A.; Weiss, Mia C.; Lee, Linus; Gitelis, Steven; Blank, Alan T.; Wang, Dian; Batus, Marta
Abstract: Background: Sarcomas are a rare and heterogeneous tumor group composed of a variety of histologic subtypes. Targeted next-generation sequencing (NGS) of bone and soft tissue sarcomas is a nascent field with limited evidence for its use within clinical practice. Therefore, further research is needed to validate NGS in sarcoma and assess the clinical utility of these techniques with the hope of improving treatment options. Methods: Comprehensive molecular profiling with NGS was performed on 136 tumors (116 soft tissue, 20 bone) using two commercial vendors. Patient records were retrospectively reviewed, and the clinical impact of NGS-related findings were qualitatively analyzed to determine actionable mutations and number of changes in treatment. Results: The median age was 55.0 years (IQR 42–67 years), and most patients were non-metastatic at presentation (80.9%, n  = 110). Prior to performing NGS, 72.1% ( n  = 98) were treated with a mean 1.1 ± 1.2 lines of systemic chemotherapy. NGS identified 341 putative alterations with at least one mutation present in 89.7% ( n  = 122) of samples. In a subset of 111 patients with available TMB data, 78.7% ( n  = 107) had a low (<6 m/Mb) mutational burden. Among all 136 cases, 47.1% ( n  = 64) contained clinically actionable alterations, and 12 patients had a change in medical treatment based on NGS. Those who underwent a treatment change all had metastatic or recurrent disease; three of these patients experienced a clinical benefit. Conclusion: Most bone and soft tissue sarcomas harbor at least one genetic alteration, and it appears a sizeable number of tumors contain mutations that are clinically actionable. While a change in treatment based off NGS-related findings occurred in 12 cases, three patients experienced a clinical benefit. Our data provide further proof-of-concept for NGS in sarcoma and suggest a clinical benefit may be observed in select patients.